Teaching Narrative Reading Texts by Using MURDER Method to the Eleventh Grade Students - Anadya Kavorina (Edukasi, 2020)
Mood, understand, recall, detect, elaborate and review (MURDER) method is an alternative method which enables the students comprehending reading texts, particularly narrative texts, by collaboration working between two groups. The objectives of this study were to find out (1) the significant improvement on the eleventh grade students’ reading comprehension achievement in narrative reading texts before and after being taught by using MURDER method and (2) the significant difference on the eleventh grade students’ reading comprehension achievement in narrative reading texts between those who were taught by using MURDER method and those who were not. This study used quasi experimental design by using pretest and posttest non-equivalent groups design. There were 111 eleventh grade students of SMA Muhammadiyah 2 Palembang in academic year 2016/2017 were used as the population of this study. 57 students from two classes were taken as sample by using convenience sampling. 28 students from class XI IPA 2 were as the experimental group and 29 students from class XI IPA 1 were as the control group. In collecting the data, multiple choice tests were used in pretest and posttest to experimental and control groups. The data of pretest and posttest were analyzed by using independent sample t-test and paired sample t-test in SPSS program. The findings showed that the p-output from independent sample t-test was lower than 0.05 and the result of p-output from paired sample t-test was lower than 0.05. It means that MURDER method can be implemented as one of alternative method in teaching narrative reading texts.